Zinc tolerance of freshwater diatoms isolated from sites with zinc pollution; and pH effect on zinc toxicity - Hedenborg, Amanda (2016)
The aim with this study was to observe the zinc (Zn), tolerance for different strains isolated from sites with Zn pollution and to observe if lower pH decreases the Zn toxicity. Another aim was to see if malformations could be an indicator for Zn pollution.